EDITORIAL - Hayes, Grahame (PINS-Psychology in Society, 2026)
Although the four articles in this edition of PINS are quite diverse, there is an interlinking thread which runs through them, and it is the idea of identity. While Ronnie Miller’s complex and fascinating theoretical account of understanding least easily fits the mould of identity, his account of the agentic elements involved in understanding, non-understanding, and not-understanding, certainly bear on the question of what it means to be a person. Quoting Gadamer who writes that "understanding is possible only if one forgets oneself", Miller engages us in a discursus of who (agent, self, other, ego) does the understanding, and what sort of psychological interaction would understanding entail. Miller’s article (the second part of which will appear in PINS 29) re-invigorates the psychological and human (person) dimensions of cognitive psychology, which often seems too ready to escape into a form of abstract individualism. Miller not only avoids the theoreticism of much cognitive psychology, and cognitive science for that matter, but instead thinks through the methodological implications of understanding when he says, "Method is the externalisation or objectification of consciousness and the reason why we cannot deal in neutral facts or theory free data is because to do so is to eliminate consciousness".